1997
DOI: 10.1073/pnas.94.2.657
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor activation induces nuclear targeting of cyclooxygenase-2, basolateral release of prostaglandins, and mitogenesis in polarizing colon cancer cells

Abstract: Nonsteroidal antiinf lammatory drugs reduce the risk of colon cancer, possibly via cyclooxygenase (COX) inhibition. The growth factor-inducible COX-2, which is overexpressed in neoplastic colonic tissue, is an attractive target to mediate this effect. Herein we have exploited the ability of a human colon cancer cell line, HCA-7 Colony 29, to polarize when cultured on Transwell (Costar) filters to study COX-2 production and the vectorial release of prostaglandins (PGs). Administration of type ␣ transforming gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
151
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(167 citation statements)
references
References 34 publications
11
151
1
2
Order By: Relevance
“…So a direct effect of the overexpressed TGF-a on the EGF-receptor seems more likely. An interrelation between COX-2 and growth factors has been shown before for TGF-a and amphiregulin (Coffey et al, 1997;Shao et al, 2004). In this regard, it is interesting that TGF-a-stimulated cells have been used for the isolation and cloning of COX-2 (DuBois et al, 1994) and shows the close interrelation between both systems.…”
Section: Discussionmentioning
confidence: 81%
“…So a direct effect of the overexpressed TGF-a on the EGF-receptor seems more likely. An interrelation between COX-2 and growth factors has been shown before for TGF-a and amphiregulin (Coffey et al, 1997;Shao et al, 2004). In this regard, it is interesting that TGF-a-stimulated cells have been used for the isolation and cloning of COX-2 (DuBois et al, 1994) and shows the close interrelation between both systems.…”
Section: Discussionmentioning
confidence: 81%
“…In other cell types, including NIH3T3 cells, there is nuclear membrane localization of COX-1 and -2 and PGE 2 (52). In addition, a transporter has been identified that mediates the influx of prostanoids across the plasma membrane (23,29), and Ca-dependent cPLA 2 can be transported to the nuclear envelope (45), Finally, growth factor-induced translocation of COX-2 to the nuclear envelope has been described (8). Furthermore, functional EP 1 , EP 3 , and EP 4 are localized to the nucleus in porcine brain and rat liver (4).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase-2 is induced in a variety of cell types by diverse stimuli including cytokines, growth factors, mito-Ž gens and tumour promoters Kujubu et al, 1991;Lee et al, 1992;DeWitt and Meade, 1993;Ristimaki et al, 1994; . Coffey et al, 1997 . In brain and spinal cord cyclooxy-Ž genase-2 is constitutively expressed McCormak, 1994;.…”
Section: Introductionmentioning
confidence: 99%